2015
DOI: 10.4103/0253-7613.153427
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of amifostine on ischemia-reperfusion injury of rat kidneys

Abstract: Objectives:Amifostine is a drug which can eliminate free oxygen radicals that appear in the body after radiation or chemotherapeutic agent exposure. It is used to decrease the renal toxicity of cisplatin. The aim of this study was to determine the role of amifostine in warm ischemia kidney model for prevention of ischemia/reperfusion injury and also to find out the mechanism for prevention from ischemia/reperfusion injury if such an effect does exist.Materials and Methods:Adult female rats (n = 40) that used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…First, we evaluated whether EGCG could alleviate early renal injury after burn in rats from two aspects: histopathology and functional indicators. According to previous literature, researchers have also discovered that AKI can lead to tubular necrosis, which subsequently impairs renal function [ 27 , 28 ]. The experiment showed that EGCG treatment significantly attenuated the renal tubule injury scores of burned rats, indicating its ability to alleviate structural damage in burned renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…First, we evaluated whether EGCG could alleviate early renal injury after burn in rats from two aspects: histopathology and functional indicators. According to previous literature, researchers have also discovered that AKI can lead to tubular necrosis, which subsequently impairs renal function [ 27 , 28 ]. The experiment showed that EGCG treatment significantly attenuated the renal tubule injury scores of burned rats, indicating its ability to alleviate structural damage in burned renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…At present, amifostine is mainly used in reducing the side effects induced by radiation therapy in the patients with malignant tumors [ 27 ]. In an in vivo study, Merter et al found that amifostine could attenuate ischemia/reperfusion injury of monkey kidneys by increasing intracellular GSH level [ 28 ]. In rat immature hippocampal neurons exposed to γ -rays, amifostine protects the neurons against the irradiation injury [ 29 ].…”
Section: Discussionmentioning
confidence: 99%